Status of Lipid Profile among the Hypertensive Patients in Bangladesh (University Heart Journal, 2014)
Back ground: Hypertension and dyslipidemia are associated with oxidative stress and are major causes of cardiovascular disease amounting to 30% of global death rate. It is widely accepted that cardiovascular disease is associated with hypertension and increased blood levels of low-density lipoprotein (LDL), total cholesterol (TC), and triglycerides. In contrast, a low level of high density lipoprotein (HDL) is a risk factor for mortality from cardiovascular disease. Hypertension is a major public health problem in developed and developing countries. Methods: This study was a cross sectional study in which 159 diagnosed hypertensive patient and 75 with normal blood pressure (normotensive) were enrolled. These patients sought a through health cheek up including blood pressure assessment between May 2012 to April 2013 in Tairunnessa Memorial Medical College and Hospital. Lipid parameter total cholesterol (TC), triglyceride (TG), low density lipoprotein ( LDLc) and high density lipoprotein (HDLc) were estimated by enzymatic colorimetric test. Results: The mean of Systolic blood pressure and Diastolic blood pressure of hypertensive were higher than normotensive (p